Collaborative Governance Assessment Development of Tourist Villages in Patengan Village, Rancabali District, Bandung Regency - Andre Ariesmansyah; Rifqi Khaerul Arifin (Formosa Journal of Social Sciences (FJSS), 2024)
The development of tourism villages in Patengan Village, Rancabali District has become the attention of many parties. This can be seen from the many activities that have been carried out to promote this tourism village. This collaborative governance assessment study aims to evaluate the development of tourism villages in Patengan Village, Rancabali District. This study was conducted by involving various parties, including the government, community, and academics. Based on the results of this study, it can be concluded that the development of tourism villages in Patengan Village, Rancabali District has gone well. This can be seen from the collaboration between various parties involved in the development of this tourism village. In addition, there is also a high awareness from the community about the importance of developing this tourism village. However, there are still several obstacles faced in the development of this tourism village. Some of them are lack of human resources, lack of capital, and lack of public awareness about the importance of developing tourism villages